2023
DOI: 10.1038/s41598-023-36320-z
|View full text |Cite
|
Sign up to set email alerts
|

Mapping gut parasitism patterns in a cohort of Egyptians

Abstract: In developing countries, the prevalence of intestinal parasitic infection is still significant, particularly due to geographical and socioeconomic variables. The objective of this study was to map the distribution pattern of intestinal parasitic infection in a cohort of the Egyptian population, as well as to assess associated risk factors. A cross-sectional hospital-based study was conducted on 386 patients. A single fecal specimen was collected from the study individual and examined microscopically for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…In contrast to protists infection (37.9%), the prevalence of helminths was comparatively low at 2.5%. This finding was consistent with previous GIP prevalence studies conducted in ARE [ 32 , 33 , 42 ] and other regions [ 43 ]. The reduction in the prevalence of intestinal helminths could be attributed to the implementation of anti-helminthic community-based control programs [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to protists infection (37.9%), the prevalence of helminths was comparatively low at 2.5%. This finding was consistent with previous GIP prevalence studies conducted in ARE [ 32 , 33 , 42 ] and other regions [ 43 ]. The reduction in the prevalence of intestinal helminths could be attributed to the implementation of anti-helminthic community-based control programs [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Forty percent of the 520 individuals examined in this study were infected with at least one parasite. The observed prevalence rate was comparatively lower than those previously documented in other regions of ARE, including Gharbia governorate (46.2%) [ 31 ], Zagazig district (56%) [ 42 ], and Cairo (59.6%) [ 32 ]. Nevertheless, it surpassed the prevalence among school students in Aswan (31%) [ 33 ].…”
Section: Discussioncontrasting
confidence: 69%
“…These results are consistent with other reports from several geographic regions worldwide that principally identified the subtypes ST1 to ST9 [ 91 , 92 , 93 , 94 , 95 , 96 ]. According to Nemati et al [ 11 ], the first three, ST1, ST2, and ST3, are the most frequent STs among human subjects in the Asian continent.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies in developing countries reported the following Blastocystis spp. prevalence and the dominant ST: Algeria, 7.4%—ST3 [ 98 ]; Angola, 25.6%—ST3 [ 99 ]; Azerbaijan, 45.1%—ST3 [ 100 ]; Cambodia, 55.2%—ST1 [ 101 ]; Egypt, 47.8%—ST3 [ 91 ]; India, 27.0%—ST3 [ 102 ]; Jordan, 15.0%—ST3 [ 100 ]; Malaysia, 18.5%—ST3 [ 103 ]; Nigeria, 55.5%—ST1 [ 100 ], the Philippines, 13.0%—ST3 [ 104 ]; Qatar, 71.1%—ST3 [ 26 ]; Saudi Arabia, 68.6%—ST3 [ 105 ]; Senegal, 51.7%—ST2 [ 106 ]; Sudan, 47.5%—ST1 [ 100 ]; Tanzania, 61.0%—ST1 [ 107 ]; Turkey, 24.6%—ST3 [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in these latter studies, the parasite frequency was determined via direct microscopy of fecal smears or after in vitro cultivation of stool samples, which are conventional detection methods known to significantly underestimate the true incidence of the parasite compared to molecular assays [52,53]. Recently, the prevalence of 64.0% and 37.3% have been recorded by PCR for two limited cohorts of Egyptians [54,55], but either almost all or all PCR products obtained in these surveys were not sequenced to confirm the presence of the parasite. Overall, the prevalence observed in our Egyptian cohort was similar to that determined, for instance, in large groups of individuals in West Africa, like in Senegal (80.4%) [5] or Guinea (78.0%) [6].…”
Section: Resultsmentioning
confidence: 99%